2011
DOI: 10.1007/s00210-011-0654-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective mechanisms of peroxisome proliferator-activated receptor agonists in Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common causes of dementia accounting for 50-60% of all cases. The pathological hallmarks of AD are the formation of extracellular plaques consisting of amyloid-β protein, intracellular neurofibrillary tangles of hyperphosphorylated tau proteins and presence of chronic neuroinflammation causing progressive decline in memory and cognitive functions. The current therapeutic strategies to improve memory deficits aim at preventing the formation and accumulation of amyloid-β and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 114 publications
(114 reference statements)
0
22
1
Order By: Relevance
“…PPARβ/δ seems to works as sensor of oxidative stress, this phenomenon being apparent at 3 mo age in Tg mice, typically characterized by the appearance of oxidative stress, [17][18][19][20][21][22] even though in the present study this event is not correlated with cell death, as apoptotic nuclei are not detected by TUNEL analysis at this age. Therefore, it appears that in the neocortex at 3 mo age, the increased levels of PPAR β/δ and the absence of an increase of 4-HNE adducts protect this brain area from the early perturbation of the redox status.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…PPARβ/δ seems to works as sensor of oxidative stress, this phenomenon being apparent at 3 mo age in Tg mice, typically characterized by the appearance of oxidative stress, [17][18][19][20][21][22] even though in the present study this event is not correlated with cell death, as apoptotic nuclei are not detected by TUNEL analysis at this age. Therefore, it appears that in the neocortex at 3 mo age, the increased levels of PPAR β/δ and the absence of an increase of 4-HNE adducts protect this brain area from the early perturbation of the redox status.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, their involvement in neurodegenerative Involvement of peroxisome proliferator-activated receptor β/δ (PPAR β/δ) in BDNF signaling during aging and in Alzheimer disease diseases, such as multiple sclerosis, amyotrophic lateral sclerosis, Alzheimer, Parkinson, and Huntington diseases, is well recognized. [15][16][17][18][19][20][21][22] Even though PPAR β/δ is the most abundant isotype in the developing and adult central nervous system (CNS), [23][24][25] its role in neurodegenerative diseases remains unclear. We have previously demonstrated that PPAR β/δ is crucial for neuronal maturation, and that its expression affects the BDNF signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…85,86 Further, PPAR-γ is being considered as a novel target to manage cognitive decline in AD patients. 20,87,88 PPAR-γ agonists significantly reduced spatial memory impairment induced by the amyloid burden, Aβ aggregates, Aβ oligomers, astrocytic and microglia activation. 89 Thus, prevention of the protective effect of lisinopril and telmisartan by BADGE suggests that, in addition to their antioxidative, anti-inflammatory and anticholinestrase activity, these drugs may also be acting through the PPAR-γ pathway and thus providing considerable protection in i.c.v.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, leukotriene B 4 has been identified as a physiological agonist of peroxisome proliferator-activated receptor-α (PPARα), a member of the nuclear hormone receptor family that regulates the transcription of genes involved in inflammation and lipid metabolism, including apolipoprotein (apo) A-I, apoE and low density lipoprotein receptor-related protein-1 (LRP-1) [9,10]. Activation of PPARs has been shown to upregulate Aβ clearance via apoE and LRP-1, reduce inflammation and lower cholesterol, thereby making them therapeutic candidates for the treatment of AD [11,12]. …”
Section: Introductionmentioning
confidence: 99%